Guidelines for Managing Process Safety Risks During Organizational Change. (CCPS guidelines series., 2013)
An understanding of organizational change management (OCM) - an often overlooked subject - is essential for successful corporate decision making with little adverse effect on the health and safety of employees or the surrounding community. Addressing the myriad of issues involved, this book helps companies bring their OCM systems to the same degree of maturity as other process safety management systems. Topics include corporate standard for organizational change management, modification of working conditions, personnel turnover, task allocation changes, organizational hierarchy changes, and or.